Mondo e totalità: L’approccio fenomenologico di Heidegger e Lukács - Mancini, Federico (B@belonline, 2020)
The essay proposes a theoretical comparison between two of the 20th century fundamental works, Martin Heidegger’s Being and Time and György Lukács’ History and Class Consciousness. Even in the radical philosophical diversity that characterizes the authors’ perspectives, it is possible to trace a common theoretical approach of phenomenological derivation that redefines the structures of subjectivity both individual and collective, through a paradigmatic deconstruction of the subject-object relationship. This commonality emerges by comparing some fundamental theoretical formulations contained in these two works, such as the Heideggerian concept of In-der-Welt-sein and the Lukácsian theories on totality and class consciousness.